Chile, Social Accounting Matrix, 1996 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The 1996 SAM for Chile breaks down the economy into two sectors: the productive sector which is classified in 13 different activities (agriculture, wood and paper, fishing, mining (except oil), oil, extraction and refinery, manufactures, electricity, gas and water, construction, commerce, transport and communication, other services) and the institutional sectors: private non-financial sector (households, rest of the private non-financial sector), public sector (government, public non-financial firms), financial institutions (Central Bank, private banks, other financial institutions). The sources for this SAM are official studies published by the Central Bank of Chile, a non-official study, and a non-official study prepared for internal use by the Central Bank of Chile, Ministerio de Planificación y Cooperación (MIDEPLAN) and Comisión Económica para América Latina y el Caribe (CEPAL).